2016
DOI: 10.3390/e18050175
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Chaotic Behavior of the Lower Hybrid Wave Propagation in Magnetised Plasma by Hamiltonian Theory

Abstract: Abstract:The Hamiltonian character of the ray tracing equations describing the propagation of the Lower Hybrid Wave (LHW) in a magnetic confined plasma device (tokamak) is investigated in order to study the evolution of the parallel wave number along the propagation path. The chaotic diffusion of the "time-averaged" parallel wave number at higher values (with respect to that launched by the antenna at the plasma edge) has been evaluated, in order to find an explanation of the filling of the spectral gap (Fisch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 52 publications
(61 reference statements)
0
1
0
Order By: Relevance
“…For years, a wide variety of simulation methods based on different theoretical models have been constructed to address different aspects of LHW problems. Examples include Fokker-Planck code that solves the Fokker-Planck equation to obtain the steady-state distribution function and current generation [11,12], ray-tracing or beam-tracing code based on the Wentzel-Kramers-Brillouin (WKB) approximation [13,14] that solves the propagation of the LHW, and full-wave code that solves the Maxwell equations using plasma currents to describe the propagation and mode structure of waves. Usually, different simulation approaches are combined to investigate LHW physics.…”
Section: Introductionmentioning
confidence: 99%
“…For years, a wide variety of simulation methods based on different theoretical models have been constructed to address different aspects of LHW problems. Examples include Fokker-Planck code that solves the Fokker-Planck equation to obtain the steady-state distribution function and current generation [11,12], ray-tracing or beam-tracing code based on the Wentzel-Kramers-Brillouin (WKB) approximation [13,14] that solves the propagation of the LHW, and full-wave code that solves the Maxwell equations using plasma currents to describe the propagation and mode structure of waves. Usually, different simulation approaches are combined to investigate LHW physics.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, as a result of the LH propagation in the presence of magnetic shear, the poloidal components are produced by the scattering project in the parallel direction. However, the geometrical effects might be not be sufficient to bridge the spectral-gap problem [36,50] and the experimental study performed in [21] suggested a leading role of PI in this context. Concerning the density limit in the LH current drive, the effects of ionization and resistive losses [51] as well as the LH scattering off density fluctuations have been invoked as a possible explanation [52][53][54][55][56][57].…”
Section: Introductionmentioning
confidence: 99%